PENGARUH PENERIMAAN PAJAK REKLAME DAN RETRIBUSI DAERAH TERHADAP PENINGKATAN PENDAPATAN ASLI DAERAH (PAD) DI KABUPATEN PURWOREJO - , (Politeknik Sawunggalih Aji, 2023)
Advertisement tax and regional retribution is an important contribution in supporting the increase of PAD. Regional Original Income is a very important contribution in supporting the regional economy because it acts as a source of funding and as a benchmark in the implementation of regional autonomy. With the implementation of regional autonomy it provides an opportunity for the government to explore the results of regional wealth sourced from the PAD. If PAD has increased every year, development in the regions will be carried out well. This study aims to determine the effect of advertising tax and regional retribution partially on PAD and to find out which variables are more dominant than the two variables that affect the increase in PAD in Purworejo Regency. The data used are realization reports from BPPKAD Purworejo Regency in 2016 to 2018, using multiple regression analysis and data processing using SPSS version 20.0. Based on the results of data processing, it can be seen that the regression model has no deviation in the classical assumption test. Advertising tax partially has no effect on the increase in PAD and regional retribution has an effect on PAD with a significant value of 0.007. Whereas seen from the contribution of regional retribution more dominantly influences the increase in Regional Original Revenue that is equal to 52.4%, while for advertisement tax contribution is only -18.2%. Keywords: advertising tax, regional retribution, local revenue.